Environmental friendliness of fishing gears in Kranji, Lamongan Regency - Atikasari, Meilia; Sawiji, Asri; Muslih, Toha (Journal of Marine Resources and Coastal Management, 2022)
Increasing time has made technological advances increase, including in the field of fisheries which has a positive impact on fishing business in Indonesia. Environmentally friendly fishing technology is a fishing gear that does not have a negative impact on the environment. The use of environmentally friendly fishing gear is very important to be applied in the fishing process in certain waters. This study was conducted in Kranji Village, Paciran District, Lamongan Regency. The purpose of this study is to analyse the level of friendliness of fishing gear in Kranji Village, besides the specifications, operating methods, and variety of catches. The research method used survey and in-depth interviews with related parties related to the results of research and the level of friendliness of fishing gear. The weighting determination of the level of environmental friendliness of fishing gear is based on the Food and Agriculture Organization (FAO). The results of this study shows that the purse seine fishing gear, cob nets, gill nets and payang are environmentally friendly fishing gears, while mini trawlers are non-environmentally friendly fishing gear. This indicates that the presence of trawling gear can affect the decline in fishery resources in Kranji, Lamongan Regency.